Factors affecting viral suppression or rebound in people living with HIV and receiving antiretroviral therapy in Ghana - Boateng, Anthony T.; Aboagye, James O.; Lamptey, Helena; Abana, Christopher Z.-Y.; Abaidoo-Myles, Araba; Quansah, Darius N. K.; Agyemang, Seth; Awuku-Larbi, Yaw; Ansa, Gloria; Oliver-Commey, Joseph; Ganu, Vincent; Kyei, George B.; et al. (Frontiers in Public Health, 2025)
IntroductionRegular viral load (VL) testing for people living with HIV (PLWH) is key to attaining the Joint United Nations Program on HIV/AIDS (UNAIDS) Fast-Track 95–95-95 target to end the HIV epidemic by 2030. However, VL testing remains sporadic in routine HIV care in the majority of resource-limited settings, including Ghana, except when provided through research initiatives. In this study, we measured VL among PLWH in Ghana at regular intervals and investigated factors affecting viral suppression (VS) and rebound.MethodsWe analyzed data from a hospital-based cohort enrolled in our HIV cure research. Participants were recruited from three hospitals in the Greater Accra region of Ghana. Demographic characteristics were obtained from participants’ folders, while CD4+ T cell counts and VLs were measured from blood samples collected at baseline, 6 months, and 18 months.ResultsThe study participants were predominantly women (68%) with a median age of 45 years (IQR: 21–76 years). A total of 52% of participants had been on antiretroviral therapy (ART) for more than 6 years, and 74% were following dolutegravir-based regimens. At baseline, 74% of participants had a VL of <50 copies/mL, which increased to 88% at 18 months, with 80% having a CD4+ T cell count of >350 cells/μl. Age group [<40 vs. > 40 years] (OR 2.35, 95% CI; 1.21–4.58, p = 0.012), CD4+ T cell count [>350 vs. < 350 cells/μl] (OR 4.35, 95% CI; 2.32–8.18, p < 0.001), and ART regimen [NVP based vs. DTG based] (OR 7.00, 95% CI; 1.15–42.57, p = 0.034) were associated with VS of <50 copies/mL. The overall viral rebound rate was estimated at 13.61 per 1,000 person-months (95% CI 10.52–17.74), with decreasing rates over time. Lower educational levels (up to Junior High School) were significantly associated with viral rebound (p = 0.011).ConclusionA key feature of our study was measuring VL at three time points over 2 years, which may explain the high VS levels observed. Viral rebound was linked to low education levels, highlighting the need for targeted education for PLWH with junior high school (JHS) education or less. Regular VL monitoring and the implementation of measures to prevent viral rebound, particularly among PLWH with lower education levels, will help Ghana move closer to attaining the third “95” of the UNAIDS 95–95-95 target by 2030.